Draft Annual Plan 1983-84 Volume IV General Areas Government of Assam - Planning Commission (Planning Commission, 1983)
The level of development achieved up to the base year 1979-80 was 3304 KM surfaced, and 15980 KM unsurfaced, totaling 19284 KM. The actual achievement during 1980-81 is 135 KM surfaced,564 KM unsurfaced, totaling 699 KM. The achievement during 1981-82 is 84 KM surfaced 510 KM unsurfaced totaling 594 KM.
Government of Assam, Planning and Development Department